Pre-service Biology Teachers Academic Performance and Retention using Jigsaw Presentation Learning Strategy - Usman Musa (Universal Education, 2025)
There has been a paradigm shift in the instructional approaches of engaging the learner from teacher-centered approach to students-centered approach. Lecture method of teaching has not been so helpful in improving student performance and retention. Student-centered approach such as jigsaw cooperative learning strategy has been identified to be effective in advancing communication skills, interpersonal skills as well as academic performance and retention. This study investigated pre-service Biology teacher’s academic performance and retention using jigsaw cooperative presentation learning strategy (JCPLS) in Kebbi and Sokoto States Universities, Nigeria. The study employed quasi-experimental research design; one hundred and twenty seven (127) pre-service Biology teachers were purposively selected as the sample for the study. Lower Invertebrate performance test (LIPT) with option A-D forms the instrument for the study. LIPT instrument was validated by 3 experts, the pilot testing result of LIPT shows the reliability index of .89 using PPMC. Two objectives, research questions and null hypotheses guided the study. The results revealed that experimental group to which JCPLS was used in teaching Lower Invertebrate Course performed better than the control group to which lecture method was used. Also the results showed that there was no significant difference between post test and follow-up test scores in experimental group. It was concluded that JCPLS is effective in improving academic performance and retention of Lower Invertebrate Course content among pre-service biology teachers. It was recommended among others that lecturers should utilize JCPLS in teaching Lower Invertebrate Course and other courses.